Standardization and Safety Evaluation of Kofsap Sugar-Free Syrup: Integrating Ayurvedic Principles with Modern Analytical Techniques (AYUSHDHARA, 2025)
Ayurveda, a holistic medicinal system, treats cough as an imbalance of Kapha and Vata doshas, employing therapies to soothe respiratory passages, reduce inflammation, and promote mucus expulsion. Kofsap Sugar-Free Syrup, developed by Sitaram Ayurveda, is a polyherbal formulation designed for effective cough relief without added sugars, catering to diabetic and health-conscious individuals. Materials and Methods: The study assessed Kofsap SF syrup quality, safety, and efficacy through organoleptic, physicochemical, phytochemical, microbial, and Gas Chromatography-Mass Spectrometry (GC-MS) analyses, adhering to Ayurvedic Pharmacopoeia of India standards. Results: Kofsap SF syrup exhibited acceptable organoleptic traits, including a dark brown colour, characteristic herbal odour, and slightly sweet-astringent taste. Physicochemical analysis confirmed stability with a pH of 5.94, refractive index of 1.339, and low moisture content (5.35%). Phytochemical screening identified carbohydrates, proteins, glycosides, steroids, flavonoids, phenols, saponins, and alkaloids. GC-MS analysis revealed key bioactive compounds, including cyclohexanol (36.665%) and thymol (25.460%), with antitussive, anti-inflammatory, and antimicrobial properties. Microbial tests confirmed safety, with no pathogens detected and a total bacterial count below 10 cfu/mL. Conclusion: Kofsap SF syrup demonstrates high quality, safety, and therapeutic potential, validated by comprehensive standardization. Its stability, rich phytochemical profile, and absence of contaminants position it as an effective Ayurvedic remedy for cough relief, aligning traditional wisdom with modern healthcare demands.